The coupling between gaze behavior and opponent kinematics during anticipation of badminton shots - Alder, D.; Ford, P. R.; Causer, J.; Williams, A. M. (Human Movement Science, 2014)
Purpose: We examined links between the kinematics of an opponent`s actions and the visual search behaviors of badminton players responding to those actions. Method: A kinematic analysis of international standard badminton players (n = 4) was undertaken as they completed a range of serves. Video of these players serving was used to create a life-size temporal occlusion test to measure anticipation responses. Expert (n = 8) and novice (n = 8) badminton players anticipated serve location while wearing an eye movement registration system. Results: During the execution phase of the opponent`s movement, the kinematic analysis showed between-shot differences in distance traveled and peak acceleration at the shoulder, elbow, wrist and racket. Experts were more accurate at responding to the serves compared to novice players. Expert players fixated on the kinematic locations that were most discriminating between serve types more frequently and for a longer duration compared to novice players. Moreover, players were generally more accurate at responding to serves when they fixated vision upon the discriminating arm and racket kinematics. Conclusions: Findings extend previous literature by providing empirical evidence that expert athletes` visual search behaviors and anticipatory responses are inextricably linked to the opponent action being observed.